Kepemimpinan Islami dalam Meningkatkan Kinerja Pegawai: Mini Literature Review - Wahyu Derajat Shobastian; Qurratul Aini (Benefit: Jurnal Manajemen dan Bisnis, 2020)
The purpose of this article is to determine the effect of Islamic leadership in improving employee performance. The method used in this article is to use a simple article review or a mini literature review based on finding answers to scientific questions according to the purpose of this article used in the database (Emerald, Researchgates and Google Scholar) which article a decade. The Results is Islamic leadership which consists of four characteristics and can be expanded to 25 characteristics can influence the culture of Islamic organizations so that the employee has an Islamic work ethic that can ultimately improve the performance of the employee. So, Islamic leadership can improve employee performance by being mediated by Islamic work ethics through organizational culture.Keywords: Islamic leadership, employee performance, Islamic work ethics